Photo‐Induced Ruthenium‐Catalyzed C−H Arylations at Ambient Temperature. Issue 41 (17th August 2020) - Korvorapun, Korkit; Struwe, Julia; Kuniyil, Rositha; Zangarelli, Agnese; Casnati, Anna; Waeterschoot, Marjo; Ackermann, Lutz
Abstract: Ambient temperature ruthenium‐catalyzed C−H arylations were accomplished by visible light without additional photocatalysts. The robustness of the ruthenium‐catalyzed C−H functionalization protocol was reflected by a broad range of sensitive functional groups and synthetically useful pyrazoles, triazoles and sensitive nucleosides and nucleotides, as well as multifold C−H functionalizations. Biscyclometalated ruthenium complexes were identified as the key intermediates in the photoredox ruthenium catalysis by detailed computational and experimental mechanistic analysis. Calculations suggested that the in situ formed photoactive ruthenium species preferably underwent an inner‐sphere electron transfer. Abstract : Light‐enabled ruthenium‐catalyzed C−H activation enables direct arylations at room temperature. Biscyclometalated ruthenium intermediates were identified as photoredox catalysts through a metal‐to‐ligand charge transfer (MLCT), intersystem crossing (ISC) and inner‐sphere electron transfer (ISET) manifold.